(untitled) (BIRDEM Medical Journal, 2019)
Background: Growth assessment is an essential component of pediatric health surveillance because almost any problem within the physiologic, interpersonal and social domains can adversely affect growth. The most powerful tool in the growth assessment is the growth chart. Growth parameters of children are usually interpreted in relation to international standards like the National Center for Growth Statistics (NCHS) and Centers for Disease Control and Prevention (CDC) Growth Charts of 1977 and 2000, respectively. In 2007, the World Health Organisation (WHO) published a new set of growth charts believed to be applicable to children reared healthily in all parts of the globe. The aim of current study was determine the growth pattern of school children in Sylhet using the CDC standards and WHO standards. Methods: A Comparative cross-sectional study was done in the department of paediatrics, Sylhet MAG Osmani Medical College Hospital from July, 2012 to Dec, 2012. Multi-stage random sampling technique was adopted for the survey. This study was carried out in selected primary schools in Sylhet Metropoliton City area. The participants were healthy school children, aged 6 to 11 years who was purposively selected. A total of 504 children were included into this study. The primary end point was to determine weight, height and body mass index (BMI) and the secondary end point was to compare the values using 2000 CDC standards and 2007 WHO standards. Results: The mean weights, height and BMI of the studied child were lower from CDC and WHO standards but closer with the WHO standards and wider from CDC. The weight Z-scores have got closer on the two reference charts for both male and female but differ at age 6 and 7 years. The median height Z-scores were almost closer to the median for male and female at all different ages on both CDC and WHO charts. The median BMI Z-scores for both sexes were below the reference values on both CDC and WHO charts. The prevalence of underweight and stunting were higher in both sexes when determined using the CDC standards compared to WHO standards. Conclusion: The WHO references would under diagnose under-nutrition and over-diagnose overweight/obesity in the population studied. However, this study results are closer to the WHO reference and wider from the CDC standards. Birdem Med J 2019; 9(1): 35-43